Perspectivas da licença-paternidade: corresponsabilidade no trabalho de cuidado sob à luz dos direitos fundamentais trabalhistas - Carvalho, Mariana (2024)
This research deals with traditional forms of family and social organization, as well as the sexual division of professional work and care work, whose internal patterns and rules are perpetuated between generations and are considered natural and innate to people. However, it will be shown that these aspects are cultural and mutable, in other words, it changes as societies evolve. Thus, although the reflections of the patriarchal model are still present, the fact is that today society is increasingly demanding parity of rights and duties between men and women, which includes the division of care work and the need for greater male participation in this area. In this context, increasing the length of paternity leave is essential to foster equality between men and women, as provided by the Brazilian Federal Constitution, as well as to provide a balance in the execution of family responsibilities and the exercise of the right and duty of fathers to care for their children. In addition, it will be pointed out how parental leave is a valuable and significant right for fathers and mothers to remain close to their children and actively participate in their upbringing, strengthening bonds, affective ties, and quality family time